Knowledge and attitudes of South African stakeholders regarding conservation of the African penguin (Spheniscus demersus) - Abernethy, D.A. (University of Pretoria, 2023)
Dissertation (MSc (Wildlife Health, Ecology and Management))--University of Pretoria, 2023.